THE GENUS FRULLANIA (HEPATICAE: FRULLANIACEAE) IN BALI - Ida Haerida (PTTI, 2015)
A first study of Frullania in Bali indicate that seven species can be recognized. They are F. gaudichaudii (Nees & Mont.) Nees & Mont., F. gracilis (Reinw., Blume & Nees) Dumort., F. junghuhniana Gottsche., F. meyeniana Lindenb., F. moniliata (Reinw., Blume & Nees) Mont., F. ornithocephala (Reinw. et al.) Nees and F. ternatensis Gottsche. Figure of Frullania moniliata are presented. Notes on description to the genus, key to the species, diagnostic characters, as well as distribution of the species are given.